Comparative analysis of high-sensitivity cardiac troponin I and T for their association with coronary computed tomography-assessed calcium scoring represented by the Agatston score - Rusnak, Jonas; Behnes, Michael; Henzler, Thomas; Reckord, Nadine; Vogler, Nils; Meyer, Mathias; Hoffmann, Ursula; Natale, Michèle; Hoffmann, Julia; Hamed, Sonja; Weidner, Kathrin; Lang, Siegfried; et al. (European journal of medical research, 2017)
This study evaluates the association between high-sensitivity cardiac troponin I (hs-cTnI) and T (hs-cTnT) and coronary calcium concentration (CAC) detected by coronary computed tomography (CCT) and evaluated with the Agatston score in patients with suspected coronary artery disease (CAD).